Crash my party [compact disc] - Bryan, Luke (Capitol Nashville, 2013)
ACM Entertainer of the Year Luke Bryan returns with the follow-up to his successful album Tailgates & Tanlines. His fifth full-length release includes the country hit single Crash My Party.